The Influence of Economic Literacy, Family Economic Education, and Social Environment on Entrepreneurial Intention: A Case Study of Students of the Faculty of Agriculture, Sam Ratulangi University, Manado - Alexander Kaunang; Pauline H.P.Tan (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2024)
Entrepreneurial intention is important for young people, especially university graduates, because with the knowledge they have, they are potential entrepreneurs, can help the economic welfare of the wider community, through the creation of new jobs, opportunities to invest, and increase productivity. From the results of a tracer study in November 2023 (UNSRAT Faperta, 2023), it shows that many graduates of the Faculty of Agriculture UNSRAT from the 2020-2022 class are still unemployed, waiting for the CPNS test, or working as private employees. In fact, these graduates have the potential to create jobs, especially with knowledge in agriculture and digital skills. This study was conducted on 160 students to analyze the influence of economic literacy, family economic education, and social environment on students' interest in entrepreneurship, in order to encourage them to utilize their skills to become entrepreneurs. The results of the study showed that all of these variables significantly influenced the interest in entrepreneurship of students at the Faculty of Agriculture UNSRAT Manado.